Teachers’ Perception toward the Policy of Eliminating National Exam - Aziz, Abd; Rohman, Khabibur (Universitas Islam Negeri Raden Intan Lampung, 2020)
This study analyzed teachers' perceptions toward the national exam elimination policy, starting in 2020 at both the primary and secondary school levels. This research implemented an explorative qualitative approach to teachers' perceptions of eliminating the national exam issue. This research employed interviews with 21 purposively chosen informants who were teachers of primary and secondary schools. Accordingly, this research also employed a secondary data collection method in the form of an online survey of 190 formal education teachers. The result of the study showed that the teachers argued about the national exam in many aspects. The curriculum is considered too narrow, too much attention for cognitive aspect, and does not accommodate students’ potential diversity. The national exam is also defective on both juridical and theoretical. However, eliminating the national exam worried the teachers regarding the drop in students' learning motivation and the gap in schools’ education quality. Teachers need to know that national exams are not the only reason to make students study hard. Teachers should foster students' internal motivation by emphasizing that learning should not occur because of exams.